The role of translators in cross-language qualitative research in psychology. Issue 1 (2nd January 2021) - de Vos, Jaqueline; Nokele, Bulelwa
Abstract: Qualitative researchers in the field of psychology are increasingly conducting research in multilingual social contexts. Literature on cross-language research emphasises, however, that issues on the role of translators and information on translation processes in such studies are often neglected or omitted in research reports, which may affect the trustworthiness of such studies. The aim of this case study was to investigate the role of translators in cross-language qualitative research, specifically in the field of psychology. Five postgraduate students (master's and doctoral students), enrolled at a South African university (SAU), participated in the study. Data were collected through semi-structured e-mail, telephone and/or face-to-face interviews and were transcribed by the researcher who collected the data. In addition, unpublished dissertations (five) and theses (two) were also uploaded from the SAU's online catalogue to explore, from another viewpoint, whether postgraduates' research reports made any mention of the role of translators and/or translation processes in their research. Data were analysed by means of thematic data analysis using a qualitative data analysis software program, ATLAS.ti. The main themes that emerged from this study are discussed in this article. Finally, recommendations are made for future translation research and practice.